Combined diffusion-weighted imaging and dynamic contrast-enhanced MRI for differentiating radiologically indeterminate malignant from benign orbital masses. Issue 10 (October 2017) - Xu, X.-Q.; Qian, W.; Ma, G.; Hu, H.; Su, G.-Y.; Liu, H.; Shi, H.-B.; Wu, F.-Y.
Abstract : Aim: To evaluate the performance of the combination of diffusion-weighted (DW) and dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) for differentiating radiologically indeterminate malignant from benign orbital masses. Materials and methods: Sixty-five patients with orbital masses (36 benign and 29 malignant) underwent DW and DCE MRI examinations for pre-treatment evaluation. The apparent diffusion coefficient (ADC) was derived from DW imaging data using the mono-exponential model. The volume transfer constant (K trans ), the flux rate constant between the extravascular extracellular space and the plasma (Kep ), and the extravascular extracellular volume fraction (Ve ) were calculated using modified Tofts model. Differences in quantitative metrics were tested using independent-samples t test. Receiver operating characteristic (ROC) curve analyses were used to determine and compare the diagnostic ability of each significant metric. Results: The malignant group demonstrated significantly lower ADC (0.711±0.260 versus 1.187±0.389, p <0.001) and higher Kep values (1.265±0.637 versus 0.871±0.610, p =0.008) than the benign group. Optimal diagnostic performance (area under the ROC curve [AUC], 0.941; sensitivity, 0.966; specificity, 0.917) could be achieved using combined ADC and Kep values as the diagnostic index. The diagnostic performance of the combination of ADC and Kep was significantly better than Kep alone ( p =0.006). Compared with ADC alone, combined ADC and Kep values also showed higher AUC (0.941 versus 0.898), although the difference did not reach statistical significance ( p =0.220). Conclusion: Kep and ADC could help to differentiate radiologically indeterminate malignant from benign orbital masses. The combination of DW and DCE MRI might improve the differentiating performance. Highlights: Malignant orbital mass demonstrated significantly lower ADC than benign mimics. Malignant orbital mass showed significantly higher Kep than benign mimics. Both DCE MR and DW imaging could help to differentiate radiologically indeterminate malignant from benign orbital mass. Combination of DW and DCE MR imaging might improve the differentiating performance.